Mufti - McNeile, H. C. (Herman Cyril), 1888-1937 (Salt Lake City, UT : Project Gutenberg, 2008)
"Mufti" by H. C. McNeile is a novel written in the early 20th century. The book is set during World War I and follows Derek Vane, an officer in the army, and his interactions with various characters, introducing themes of war, love, and the search for meaning amidst chaos. The story juxtaposes the brutal realities of warfare with moments of light-heartedness and deep emotional reflection. The opening of the novel presents a series of scenes in the wartime setting that highlight the senses of futility and disillusionment felt by the soldiers. We meet Derek Vane, who is depicted relaxing in a makeshift camp, seemingly detached from the surrounding war, while fellow officers engage in playful banter. The narrative shifts to a dramatic air attack, revealing the stark reality of war with the deaths of enemy pilots, which elicits a mix of indifference and reflection on the events' meaning for those who survive. As Vane continues to navigate the complexities of his experiences and relationships, particularly with a V.A.D. named Margaret Trent, the novel hints at a deeper examination of the characters' emotional transformations as a result of their wartime experiences. (This is an automatically generated summary.)
Release date is 2008-03-29
E-text prepared by Al Haines
Keywords: World War, 1914-1918 -- Fiction